2022
DOI: 10.1097/mpg.0000000000003422
|View full text |Cite
|
Sign up to set email alerts
|

Perianal Crohn Disease Is More Common in Children and Is Associated With Complicated Disease Course Despite Higher Utilization of Biologics

Abstract: Background and Objectives:Both perianal and pediatric-onset Crohn disease (CD) disease are associated with complicated disease course and higher drug utilization. we aimed to explore the differences between pediatric and adult-onset perianal CD and their disease course.Methods:We included all patients with newly diagnosed CD from 2005 to 2019 at two Israeli Health Maintenance Organizations, covering 78% of the population. A combination of ICD-9 codes, radiology and procedures was used to define fistulizing per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…P erianal Crohn's disease affects up to 40% of adults and 9% to 30% of pediatric patients and is associated with worse disease outcomes, including increased hospitalizations and the need for surgery. [1][2][3][4][5][6][7] Perianal fistulizing disease is a severe phenotype of perianal Crohn's disease, affecting 20% to 25% of both adult and pediatric patients. 3,[8][9][10][11][12][13] Perianal fistulizing Crohn's disease is heterogenous and can involve the anus, perineum, or vagina.…”
Section: Principales Medidas De Resultadomentioning
confidence: 99%
See 1 more Smart Citation
“…P erianal Crohn's disease affects up to 40% of adults and 9% to 30% of pediatric patients and is associated with worse disease outcomes, including increased hospitalizations and the need for surgery. [1][2][3][4][5][6][7] Perianal fistulizing disease is a severe phenotype of perianal Crohn's disease, affecting 20% to 25% of both adult and pediatric patients. 3,[8][9][10][11][12][13] Perianal fistulizing Crohn's disease is heterogenous and can involve the anus, perineum, or vagina.…”
Section: Principales Medidas De Resultadomentioning
confidence: 99%
“…10,42,43 The lower rate of proctectomy may be related to more successful healing rates with local perianal intervention, less duration of disease burden, or differences in treatment strategies for pediatric and adult patients. 7 For example, one large cohort study found that 64% of pediatric Crohn's disease patients received treatment with a biologic, compared to 49% of adult patients. 25 This study also found that increased duration of biologic treatment was associated with a lower need for abdominal surgery in both patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…One of the unmet needs in pCD management is the lack of a clinical index that can be easily utilized by patients. Given that pCD is more common in pediatric patients [ 20 ], a simple, child-friendly tool is warranted. In 1992, an anal disease activity index was developed for use in the outpatient clinic or at the patient’s bedside [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with data highlighting the role of perianal disease at onset as a risk factor for disease progression. [33][34][35] Recently, a systematic review analyzing prognostic risk factors in CD identified small bowel disease location, elevated levels of anti-Saccharomyces cerevisiae antibodies, and polymorphisms in the NOD2/CARD15 genes as prognostic factors of a worse prognosis in pediatric CD. 6 Our research did not include an autoantibodies profile and genetic evaluation because they were unavailable in most patients.…”
Section: Discussionmentioning
confidence: 99%